KAJIAN YURIDIS BATASAN DOKTER DALAM MELAKUKAN TINDAKAN MEDIS YANG BUKAN KEWENANGANNYA DI TINJAU DARI UNDANG-UNDANG NO.29 TAHUN 2004 TENTANG PRAKTEK KEDOKTERAN - Alfred Sutrisno; Nanda Dwi Rizkia; Hardi Fardiansyah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
A doctor is required to carry out his obligations and be responsible for every effort in medical action against patients. However, some doctor's mistakes occur due to negligence or negligence. Errors or omissions made by doctors when treating patients are known in medical science as Medical Malpractice. Errors or omissions that cause harm to the patient. The relationship between doctor and patient seen from the perspective of civil law is an engagement relationship that originates from agreements and laws, where the relationship between the health service provider (medical service) as a medical action and the recipient of health services, namely the patient. The method used in this research is normative juridical research method. With a legal approach, a case approach and a conceptual approach. Data collection techniques with library data and laws and regulations. The results of the research limit doctors are allowed to take medical actions that are not within their competence, the medical profession must first have STR and SIP as stipulated in Article 29, Article 36, Law Number 29 of 2004 concerning Medical Practitioners, doctors are not allowed to take medical action those who are not competent as long as they do not have a competency certificate for the recognition of what they have obtained during the educational process, and receive additional training to obtain these competencies, and carry out the referral process if they are unable to carry out patient examination and treatment. second, the settlement process is carried out first to MKDKI to determine violations of medical disciplines and forward to MKEK to determine ethical violations and impose ethical sanctions, Article 29 of Law Number 36 of 2014 Concerning Health, provides an alternative settlement through mediation, and if it is suspected of committing a crime the crime is forwarded to the competent authorities Article 66 paragraph (3) of Law Number 29 of 2004 concerning Medical Practitioners. Therefore, doctors must always be guided by professional standards and standard operating procedures in carrying out medical practices.